Overview of the major classes of new psychoactive substances, psychoactive effects, analytical determination and conformational analysis of selected illegal drugs - Lukić Vera (De Gruyter, 2021)
The misuse of psychoactive substances is attracting a great deal of attention from the general public. An increase use of psychoactive substances is observed among young people who do not have enough awareness of the harmful effects of these substances. Easy access to illicit drugs at low cost and lack of effective means of routine screening for new psychoactive substances (NPS) have contributed to the rapid increase in their use. New research and evidence suggest that drug use can cause a variety of adverse psychological and physiological effects on human health (anxiety, panic, paranoia, psychosis, and seizures). We describe different classes of these NPS drugs with emphasis on the methods used to identify them and the identification of their metabolites in biological specimens. This is the first review that thoroughly gives the literature on both natural and synthetic illegal drugs with old known data and very hot new topics and investigations, which enables the researcher to use it as a starting point in the literature exploration and planning of the own research. For the first time, the conformational analysis was done for selected illegal drugs, giving rise to the search of the biologically active conformations both theoretically and using lab experiments.